COMMAND AND CONTROL SYSTEM OF THE COUNTRY’S DEFENSE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article reveals the nature and content of the Defence of the country and compares the nature of the leadership, command, and control concepts. It also reveals the purpose and content of the leadership, command, and control system. Based on this research, the author offers a definition of the leadership, command, and control system of the country's defence.